Modeling of fiber opticsensor based on backscattered signal using MATLAB - Mukhzeer Mohammad Shahimin; Syamimi Azizan (Penerbit Universiti Malaysia Perlis, 2013)
The book focuses on simulation of distributed fiber optic sensors based on Brillouin scattering for temperature and tsrain sensing.